Familias uruguayas con maltrato infantil: estresores y apoyo social en contexto de pobreza - Fernández Rodríguez, María Eugenia (2022)
The aim of this paper is to describe a group of families of a low socio-economic status in which child abuse and sexual abuse has been identified, linking such infringement of children rights with family stressors and social support to analyze the implications such link has for psychosocial interventions. The sample was composed by 40 adults who had children and adolescents under their care who receive help from services specialized in child abuse in Uruguay. It was found that the families studied had high socioeconomic vulnerability, childcare mainly done by women, children who had experienced polyvictimization, a high number of stressors and a low perception of social support. Conclusions drawn outline the importance of considering these variables when designing intervention programs that focus on promoting changes in parental practices that can be long lasting.